An Afterthought on the "Real Cost–Opportunity Cost" Dispute and Some Aspects of General Equilibrium under Conditions of Variable Factor Supplies - Vanek, Jaroslav (Review of Economic Studies, 1959)
An Afterthought on the "Real Cost—Opportunity Cost" Dispute and Some Aspects of General Equilibrium Under Conditions of Variable Factor Supplies Get access Jaroslav Vanek Jaroslav Vanek Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 3, June 1959, Pages 198–208, https://doi.org/10.2307/2295748 Published: 01 June 1959